Розробка знання-орієнтованого методу побудови рекомендацій з урахуванням старіння знань - Чмутов, Д. С. (ХНУРЕ, 2023)
Recommendation systems are an important component of many ecommerce websites and online marketplaces, helping users find products and services that match their interests and preferences. However, traditional recommendation systems often rely on user behavior data, such as browsing and purchase history, to generate recommendations. While these methods can be effective, they often lack the ability to provide explanations for the recommendations, which can lead to reduced user trust and satisfaction.